Effect of the Substitution of Oil for Natural Gas on Air Quality, generated in the company Cantarana, Chimbote, Peru, 2018-2020 (SCIÉNDO INGENIUM, 2021)
The replacement of R500 oil by natural gas in air quality and energy costs in the production of fishmeal was evaluated at the Cantarana de Chimbote company from 2018-2020. Both particulate matter (PM2.5) and hydrogen sulfide (H2S), using high volume air collectors, gravimeter, flow meter and fluorescência concentrations (μg/m³) were quantified, then projected with equivalences of calorifica energy, fuel consumption and market rates. The results showed that H₂S and PM2.5 grew as residual oil consumption increased 500 (gal/day) from 1.3 to 7.0 and from 2.61 to 44.97 μg/m³ respectively at speeds of 0.0017 and 0.0091 μg/m³ per gallon consumed of oil per day. With natural gas, H2S and PM2.5 showed a reduction from 0.0270 to 0.1452 and from 0.0415 to 0.7136 μg/m³, corresponding to 97.2% and 98.41% respectively, and 15.49% of the total cost was reduced with energy performance of 15.83%. The study shows that the replacement of R500 oil by natural gas projects a permanent positive environmental and economic effect.
Keywords: Substitution; natural gas; R500 oil; air quality; costs reduction